Assessment of demographic characteristics of patients with tuberculosis and treatment profile of revised national tuberculosis control programme in Purba Bardhaman district of West Bengal - Ghosh, Kalyan; Lama, Manoj (International Journal Of Community Medicine And Public Health, 2022)
Background: Tuberculosis is a communicable disease caused by Mycobacterium tuberculosis bacteria spread by droplet infection. India is classified to be among those with a high TB burden, contributing 26% of the total TB cases, globally. The objective of this study is to access the clinical and demographic characteristics of patients with tuberculosis to determine the nature of disease, its co-morbidities, and treatment profile of the patients attending the revised National TB control programme clinics. Method: This study was carried out with data collection from the District Tuberculosis Office (DTO) section of Purba Bardhaman district, West Bengal. Data relevant to the study were collected for four consecutive years, from 2017 to 2020, and were analysed using suitable statistical software. Results: In the year 2017, 2018, 2019 and 2020, there were 6569, 5534, 5964 and 4012 reported cases of TB, respectively. Out of the total cases, 73.78% were male patients. It was observed that 97.24% patients were aged ≥15. Majority of the patients, 73.97%, had pulmonary TB. 1.92% cases had drug resistance tuberculosis (DRTB). The comorbid conditions associated with TB revealed that 7.58% TB patients had diabetes and only 0.48% cases had TB-HIV. The rate of successful treatment was 88.49%. The average rate of mortality was found to be 5.27% of reported cases. Conclusions: There was a significantly high proportion of male patients afflicted with TB in the region under study and the patients ≥15 years were mostly affected. The average rate of mortality was had increased in each year from 2017 to 2020.